2007
DOI: 10.1159/000111028
|View full text |Cite
|
Sign up to set email alerts
|

Upper Gastrointestinal Crohn’s Disease

Abstract: Symptomatic gastroduodenal manifestations of Crohn’s disease are rare, with less than 4% of patients being clinically symptomatic. Gastroduodenal involvement may, however, be found endoscopically in 20% and in up to 40% of cases histologically, most frequently as Helicobacter pylori-negative focal gastritis, usually in patients with concomitant distal ileal disease. In practice, the activity of concomitant distal Crohn’s disease usually determines the indication for therapy, except in the presence of obstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 89 publications
0
30
0
2
Order By: Relevance
“…Moreover, the claims databases lack ‘daily practice’ clinical data, which would be preferred to be more precise with regard to flares, location and disease activity. For instance, the only indication for PPIs in IBD is upper gastrointestinal involvement in CD, was not evaluated in this study because the positive predictive value of ICD codes for disease location is poor (50–75%), and this misclassification could only possibly happen in about 5% of the subjects. One of the major concerns was the use of steroids, which are sometimes combined with PPIs due to the risk of peptic ulcer disease (mostly increased when combined with NSAIDs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the claims databases lack ‘daily practice’ clinical data, which would be preferred to be more precise with regard to flares, location and disease activity. For instance, the only indication for PPIs in IBD is upper gastrointestinal involvement in CD, was not evaluated in this study because the positive predictive value of ICD codes for disease location is poor (50–75%), and this misclassification could only possibly happen in about 5% of the subjects. One of the major concerns was the use of steroids, which are sometimes combined with PPIs due to the risk of peptic ulcer disease (mostly increased when combined with NSAIDs).…”
Section: Discussionmentioning
confidence: 99%
“…The most potent of these drugs, proton pump inhibitors (PPIs), supplanted histamine2‐receptor antagonists (H2Ra) in use and are currently the first‐choice therapy for peptic ulcer disease and gastro‐oesophageal reflux disease. The prevalence of their chronic use has increased and appears widely used in IBD patients for the indications mentioned above or for upper GI involvement with CD, which accounts for less than 5% of these patients. Proton pump inhibitors are generally considered very safe, but recent studies have identified potential detrimental effects .…”
Section: Introductionmentioning
confidence: 99%
“…The immunopathogenesis of CD reflects dysregulated interaction among environmental factors, intestinal flora, and genetic susceptibility factors within the immune system, which triggers inflammatory activities in the colonic mucosa [1]. CD typically affects the terminal ileum but may involve any part of the intestine.…”
Section: Introductionmentioning
confidence: 99%
“…Gastroduodenal involvement usually occurs with concomitant distal small bowel or colonic disease, which determines the mode of treatment in most cases, except in the case of obstructive gastroduodenal symptoms . Isolated esophageal or gastroduodenal CD is uncommon, and there is no evidence from high‐quality studies to guide the management of such patients.…”
Section: Resultsmentioning
confidence: 99%
“…Level of agreement: a-38%, b-44%, c-18%, d-0%, e-0% Quality of evidence: III Classification of recommendation: C Gastroduodenal involvement usually occurs with concomitant distal small bowel or colonic disease, which determines the mode of treatment in most cases, except in the case of obstructive gastroduodenal symptoms. [36][37][38] Isolated esophageal or gastroduodenal CD is uncommon, 36 and there is no evidence from high-quality studies to guide the management of such patients. Standard approaches with corticosteroids and immune-modulating agents are generally applied.…”
Section: Statement 32mentioning
confidence: 99%